2021
DOI: 10.1186/s12959-021-00308-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in Syndecan-1 as a therapeutic target and a biomarker for the severity classification of COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) pneumonitis associated with severe respiratory failure is associated with high mortality. The pathogenesis of COVID-19 is associated with microembolism or microvascular endothelial injuries. Here, we report that syndecan-1 (SDC-1), a component of the endothelial glycocalyx, may be a biomarker of severity classification for COVID-19 related to endothelial injury. Methods and analysis We analyzed the dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Of note, the level of eGC damage depends on the severity of the disease course: sera derived from patients with mild symptoms reduced the eGC by approximately 49%, whereas sera from patients with severe symptoms reduced the height of the eGC by > 60%. This underscores clinical observations showing correlations between disease severity and syndecan-1 levels [30,31].…”
Section: Discussionsupporting
confidence: 80%
“…Of note, the level of eGC damage depends on the severity of the disease course: sera derived from patients with mild symptoms reduced the eGC by approximately 49%, whereas sera from patients with severe symptoms reduced the height of the eGC by > 60%. This underscores clinical observations showing correlations between disease severity and syndecan-1 levels [30,31].…”
Section: Discussionsupporting
confidence: 80%
“…Elevation of the endothelial injury biomarkers, syndecan-1 and thrombomodulin (TM) in patients with sepsis is associated with intensive care unit (ICU) mortality ( 13 , 14 ). In COVID-19, reports of syndecan-1 increase are related to disease severity and have been suggested as an assessment of the clinical course of the patient ( 15 , 16 ). Soluble TM plasma elevation is also related to increased mortality in patients with COVID-19, as it marks direct endothelial cell damage ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that plasma heparanase activity and plasma heparan concentration were higher in COVID-19 patients compared to healthy controls, and that heparanase activity was significantly higher in ventilated ICU COVID patients vs. non-ICU COVID patients (62). Plasma syndecan-1 was significantly higher in COVID-19 patients classified as "critical" compared to those in the "severe" category; a difference that persisted for 14 days of ICU admission (63). A further study showed plasma HS concentrations were increased in COVID-19 patients compared to healthy controls (59,64) and were associated with the severity of disease (64).…”
Section: Coronavirus Disease 2019mentioning
confidence: 96%